2001
DOI: 10.1054/bjoc.2000.1649
|View full text |Cite
|
Sign up to set email alerts
|

Human kallikrein gene 5 (KLK5) expression is an indicator of poor prognosis in ovarian cancer

Abstract: Summary Kallikrein gene 5 (KLK5, also known as KLK-L2), located on chromosome 19q13.4, is one of the newly identified members of the kallikrein gene family, which is a subgroup of the serine protease enzyme family. In normal human tissues, KLK5 is highly expressed in skin, mammary gland and testis. Preliminary RT-PCR analysis has indicated that KLK5 is expressed in a subset of ovarian tumours. We have thus hypothesized that KLK5 may be a new prognostic indicator in ovarian cancer. We have examined the mRNA exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
63
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(70 citation statements)
references
References 18 publications
6
63
0
1
Order By: Relevance
“…Interestingly, the results obtained for KLK14 in this study are comparable to those obtained for KLK3, KLK6 and KLK15 in breast cancer (Yu et al, 1995;Anisowicz et al, 1996) and KLK4, KLK5 and KLK10 in ovarian cancer (Kim et al, 2001;Luo et al, 2001b;Obiezu et al, 2001), in that high expression of these kallikrein genes also correlated with patient prognosis. Similar to KLK14, these genes are also under steroid hormone regulation ).…”
Section: Molecular and Cellular Pathologysupporting
confidence: 84%
See 1 more Smart Citation
“…Interestingly, the results obtained for KLK14 in this study are comparable to those obtained for KLK3, KLK6 and KLK15 in breast cancer (Yu et al, 1995;Anisowicz et al, 1996) and KLK4, KLK5 and KLK10 in ovarian cancer (Kim et al, 2001;Luo et al, 2001b;Obiezu et al, 2001), in that high expression of these kallikrein genes also correlated with patient prognosis. Similar to KLK14, these genes are also under steroid hormone regulation ).…”
Section: Molecular and Cellular Pathologysupporting
confidence: 84%
“…The kallikrein genes, denoted KLK1 -KLK15, are located on chromosome 19q13.4 and encode for corresponding kallikrein enzymes, hK1 -hK15 Yousef et al, 2000b). Accumulating evidence indicates that many members of this family are differentially expressed in certain malignancies, including prostate (Rittenhouse et al, 1998;Magklara et al, 1999;Barry, 2001;Yousef et al, 2001c;Diamandis et al, 2002), testicular (Luo et al, 2001c), breast (Yousef et al, 2000a,c) and ovarian (Anisowicz et al, 1996;Diamandis et al, 2000c;Kim et al, 2001;Luo et al, 2001b;Magklara et al, 2001;Obiezu et al, 2001;Yousef et al, 2001a) cancers. Also, many kallikrein genes examined thus far are under steroid hormone regulation, further suggesting a role for these enzymes in endocrine-related tissues (Yousef and Diamandis, 2002).…”
mentioning
confidence: 99%
“…It will be of interest to determine the functions and the potential of serum biomarker development for the other members of the kallikrein family. Indeed, recent studies have shown that the expression of many kallikreins including hK4, hK5, hK6, hK7, and hK8 has emerged as being related to breast, ovarian, and other human cancers (Underwood et al, 1999;Diamandis et al, 2000;Kim et al, 2001;Yousef et al, 2003). Further studies of these kallikreins in ovarian cancer and the development of detection tools may facilitate better understanding of this family of proteases in ovarian cancer and improve the prognosis of ovarian cancer patients.…”
mentioning
confidence: 99%
“…Investigations are proceeding as sensitive and specific assays measuring the gene expression or protein mass of each newly identified member of the kallikrein family become available. Tissue expression of the kallikreins examined to date appears to be down-regulated in aggressive forms of breast cancer (hK3 (PSA) (Levesque et al, 1998), hK10 (Liu et al, 1996;Goyal et al, 1998), hK13 (Yousef et al, 2000) and hK6 (Anisowicz et al, 1996)) and up-regulated in ovarian cancer (hK4 (Obiezu et al, 2002), hK10 (Luo et al, 2001), hK5 (Kim et al, 2001), hK8 (Magklara et al, 2001) and hK6 (Tanimoto et al, 2001)). …”
mentioning
confidence: 99%